2015
DOI: 10.1001/jama.2015.15845
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Depression and Depressive Symptoms Among Resident Physicians

Abstract: IMPORTANCE Physicians in training are at high risk for depression. However, the estimated prevalence of this disorder varies substantially between studies. OBJECTIVE To provide a summary estimate of depression or depressive symptom prevalence among resident physicians. DATA SOURCES AND STUDY SELECTION Systematic search of EMBASE, ERIC, MEDLINE, and PsycINFO for studies with information on the prevalence of depression or depressive symptoms among resident physicians published between January 1963 and Septem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

55
764
17
22

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,004 publications
(906 citation statements)
references
References 71 publications
55
764
17
22
Order By: Relevance
“…1,2 A series of studies has shown high prevalence of mental health problems in medical residents in different cultural contexts, including Latin America, [3][4][5][6] as well as an increased incidence of these problems throughout the residency years. 2,7 Anxiety, depression, and problematic alcohol use are among the mental health issues experienced by medical residents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 A series of studies has shown high prevalence of mental health problems in medical residents in different cultural contexts, including Latin America, [3][4][5][6] as well as an increased incidence of these problems throughout the residency years. 2,7 Anxiety, depression, and problematic alcohol use are among the mental health issues experienced by medical residents.…”
Section: Introductionmentioning
confidence: 99%
“…2,7 Anxiety, depression, and problematic alcohol use are among the mental health issues experienced by medical residents. A recent systematic review and meta-analysis 6 including 54 studies from five continents identified an overall pooled prevalence of depression or depressive symptoms of 28.8% among medical residents, ranging from 20.9 to 43.2%, depending on the instrument used. Such rates are much higher than the prevalence of lifetime depression in the general population verified by a study evaluating more than 37,000 participants from 10 countries -showing prevalence rates ranging from 3 to 16.9%, or from 8 to 12% in most countries.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have documented a high prevalence of burnout and symptoms of depression among residents. 1,2 Despite starting medical school with mental health profiles better than similarly aged college graduates who pursued other careers, residents are more likely to have burnout and depression symptoms than age-similar peers. 1,2 A 2012 national study of 1701 residents found 50% had burnout symptoms in comparison to 31% among age-matched college graduates not studying medicine.…”
mentioning
confidence: 99%
“…3 Although less common than burnout symptoms, nearly a third (28.8%) of residents have substantial symptoms of depression, and the prevalence of depression increases during training. 1 The prevalence of burnout and depression among residents is alarming as the potential personal and professional consequences can be profound. Residents with burnout are more likely to report difficulty concentrating at work, 2 and differences in in-training examination scores across levels of emotional exhaustion (a domain of burnout) are as large as differences across years of training for internal medicine residents.…”
mentioning
confidence: 99%
“…1 The exact prevalence of mental illness among physicians is unknown, but the existing, limited studies indicate that rates of depression are higher among medical students and residents than the general population. [2][3][4] Suicide rates among practicing physicians are significantly higher than the general population, especially for female physicians. 5 A recent study found that the factors contributing to suicidal ideation may differ between residents and physicians in academic practice, 6 but that all physicians are less likely to seek help.…”
mentioning
confidence: 99%